1995
DOI: 10.1002/hc.520060617
|View full text |Cite
|
Sign up to set email alerts
|

Stereostructure of 8‐chloro‐5,6‐di(methoxycarbonyl)‐4,7‐dimethyl‐2‐ethoxy‐2‐phosphabicyclo[2.2.2]octa‐5,7‐diene 2‐oxide

Abstract: The first X-ray structure of a phosphabicyclooctadiene, together with the N M R and mass spectral characterization of its isomers, is reported. 0 1996

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…• C. Due to their more strained ring, the phosphabicyclooctadiene oxides of type 3 are indeed thermally less stable [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• C. Due to their more strained ring, the phosphabicyclooctadiene oxides of type 3 are indeed thermally less stable [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Isomers of the products 2 and 3 were characterized by 31 P, 13 C, and 1 H NMR, as well as mass spectrometry. Thermal examinations (TG, DTG, and DSC) suggested that phosphabicyclooctene oxide 2 underwent the elimination of the bridging P-moiety in the range of 270-430…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the phosphabicyclooctadienes (1), because of their more strained framework, are more suitable for use in thermo induced fragmentations than the corresponding bicyclooctene derivatives (2) [6][7][8]. Both precursors (1 and 2), however proved to be excellent in UV-light mediated phosphorylations [2,4,5].…”
Section: Introductionmentioning
confidence: 93%
“…In the past decade, the syntheses and fragmentation abilities of phosphabicyclooctadienes (1) and phosphabicyclooctenes (2) were intensively studied [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%